Recent changes in the summer distribution of the Balearic shearwater Puffinus mauretanicus off western France - Yésou, Pierre (Scientia Marina, 2003)
Surveys carried out in the 1980s showed that 8,000-10,000 Balearic shearwaters regularly gathered in inshore waters of central and northern Biscay, particularly off the coast of Vendée and in the Mor-Braz area, western France. This distribution, apparently linked to particular oceanographical conditions (thermal front), was strikingly overlapping with that of clupeid fish, particularly anchovies. Recent surveys (1999-2000) have shown that the species has become far less numerous in these "traditional" haunts. Conversely, its abundance has increased in the western Channel, some hundreds of kilometres to the North, during the 1990s. Reasons for this northward shift (e.g. changes in prey distribution due to fishing activities or water warming in Biscay) remain hypothetical and further study is needed.